2007
DOI: 10.1002/elps.200700063
|View full text |Cite
|
Sign up to set email alerts
|

Racing pigeon identification using STR and chromo‐helicase DNA binding gene markers

Abstract: Pigeon racing appeals to many in Taiwan, due in part to the potential large financial gains based on illegal betting. The races are unregulated with frequent examples of fraud, such as substitution of one bird for a substandard one. There is no test available to reliably verify the bloodline of pigeons and thus help to resolve such disputes. In this study, we describe a multiplex PCR amplification system combining 7 STR loci and a chromo-helicase DNA binding gene (CHD) marker for the identification of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…The results showed that DNA not less than 0.000977 ng (a 1 in 1024 dilution) and 0.003906 ng (a 1 in 256 dilution) can be amplified successfully with the primer pairs PG‐L81/PG‐H520 and PGD‐VNTR‐F2/PGD‐VNTR‐R1, respectively. In our previous report using nuclear STR loci in the identification for C. livia , the results showed that all the eight loci were successfully and correctly amplified when the DNA template was not less than 0.0156 ng 1. Our current data reaffirm the phenomenon that identification of the mitochondrial DNA is more sensitive than the nuclear DNA.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results showed that DNA not less than 0.000977 ng (a 1 in 1024 dilution) and 0.003906 ng (a 1 in 256 dilution) can be amplified successfully with the primer pairs PG‐L81/PG‐H520 and PGD‐VNTR‐F2/PGD‐VNTR‐R1, respectively. In our previous report using nuclear STR loci in the identification for C. livia , the results showed that all the eight loci were successfully and correctly amplified when the DNA template was not less than 0.0156 ng 1. Our current data reaffirm the phenomenon that identification of the mitochondrial DNA is more sensitive than the nuclear DNA.…”
Section: Resultssupporting
confidence: 83%
“…There has been previous examination of nuclear STR identification for pigeon species ( Columba livia ) 1. Nuclear DNA is suitable for immediate genetic relationship testing but to increase the efficiency of relationship identification and overcome the obstacles of STR identification from highly degraded DNA, it is useful to develop a system for maternal identification by mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, a sexing marker was added based on previously published sequence information (Lee et al . ; Huang et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…STRs are being developed to individually identify different species [122,[128][129][130][131][132][133][134][135][136] and should only react with the species for which they are designed although some cross reaction has been observed with human STR tests [137][138][139][140][141]. The main roadblock in the development of these tests is that the process of identifying suitable STRs, and the subsequent multiplexing and validation are expensive and time consuming.…”
Section: Future Prospectsmentioning
confidence: 99%